REVISITING A FRAGMENT OF THE EARLY HISTORY OF ISLAM: THE MYTH OF THE ORDER TO ASSASSINATE ENEMIES BY THE PROPHET - Javad Fakhkhar Toosi (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
This article studies a part of early Islam's history that seems ambiguous due to some reports. According to these reports, Prophet Muhammad issued decrees ordering of his opponents and enemies' assassination. The qualitative method has been used in the article. The article shows that there are only 4 cases that appear to have been terrorist operations. Another achievement of the article is that among these 4 cases, only one seems to be valid, and the other three are all rejected because of their chain of narrators. Also, these 4 cases, have all occurred on the battlefield and warzone, and none are indicative of terrorist operations. The article also argues that in the life-history studies of the Prophet, the basic principles and general teachings of the Prophet must be our foundations. The article refers to a general principle in the teachings of the Prophet, according to which He proclaimed that a Muslim must never assassinate. In conclusion, neither the authenticity of the reports, nor their texts are acceptable; they are contrary to the general policy of Islam in the fight against terrorism. The article suggests that the general principles and central teachings of the Prophet should be of interest to researchers in the study of early Islam history, which sometimes contain inconsistent and ambiguous reports.